Agroecology in Brazil and Italy: Comparative Analysis of the Historical Formation Process of Agroecology - Michelato Ghizelini, André Augusto; Pacini, Gaio Cesare (Studia Ecologiae et Bioethicae, 2025)
The agroecological movement emerges as an alternative to modern agriculture and the conventionalization of organic farming. It advocates for the development of agri-food systems grounded in the principles of biodiversity, the strengthening of family farming, food sovereignty, and the reconnection between rural and urban areas. Understanding agroecological experiences worldwide is essential for evaluating their progress in building sustainable agroecosystems. This article aims to comparatively analyze the development of agroecology in Brazil and Italy, highlighting similarities and differences. In Italy, 19.68% of agricultural land is dedicated to organic production, compared to only 0.4% in Brazil—a difference of 49 times. Furthermore, 8.31% of Italian farms are organic, while in Brazil, the figure is only 1.28%. Both countries have followed different paths: in Brazil, the agroecological movement became consolidated in the 1990s, driven by the involvement of NGOs and family farmers. In contrast, in Italy, the movement gained momentum in 2015, with greater engagement from the scientific community. In Italy, agroecology developed within a context dominated by organic farming, whereas in Brazil, the agroecological movement preceded the institutionalization of organic agriculture.